2005
DOI: 10.1103/physrevlett.94.037007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Superconducting Transition Temperature of the Heavy Fermion CompoundCeIrIn5in the Absence of Spin Correlations

Abstract: We report on a pressure(P )-induced evolution of superconductivity and spin correlations in CeIrIn5 via the 115 In nuclear-spin-lattice-relaxation rate measurements. We find that applying pressure suppresses dramatically the antiferromagnetic fluctuations that are strong at ambient pressure. At P = 2.1 GPa, Tc increases to Tc = 0.8 K that is twice Tc(P = 0 GPa), in the background of Fermi liquid state. This is in sharp contrast with the previous case in which negative, chemical pressure (replacing Ir with Rh) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…With increasing pressure, Tsc increases and reaches a maximum value of 1 K at around 3 GPa [7,8]. The mechanism of SC in CeIrIn5 has not been clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing pressure, Tsc increases and reaches a maximum value of 1 K at around 3 GPa [7,8]. The mechanism of SC in CeIrIn5 has not been clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…CeIrIn 5 was argued to exist far from an AFM QCP and be located at a cusp-like minimum of T sc which bridges the two superconducting domes [16]. Accordingly, superconductivity of CeIrIn 5 was proposed to be mediated by valence fluctuations rather than by spin fluctuations [16][17][18], which are more commonly taken to mediate pairing in HF superconductors (Scenario I in Fig. 1) [13,19].…”
mentioning
confidence: 99%
“…1) [13,19]. However, no solid evidence of a valence instability has been revealed in CeIrIn 5 , even though nuclear quadrupolar resonance (NQR) experiments detected some differences between the two superconducting domes [17,18]. On the other hand, analyses of nuclear spin-lattice re- [11], which applies to most Ce-based HF superconductors including CeCoIn5 and CeRhIn5 [4][5][6][7][8].…”
mentioning
confidence: 99%
“…8 Systematic nuclear magnetic resonance (NMR) investigations of the Ce115 systems have established that these superconductors have d-wave superconducting gaps, [9][10][11][12] and that antiferromagnetic (AFM) spin interactions play an active role in the superconducting pairing. [13][14][15][16] In the Pu115 systems, NMR measurements show d-wave-like superconducting gap behavior, 17,18 with T c 's an order of magnitude higher than those for the Ce115. In heavy-fermion 115 systems, recent systematic NMR experiments have suggested that AFM XYtype anisotropy is more favorable for d-wave superconductivity than Ising-type or isotropic fluctuations.…”
Section: Introductionmentioning
confidence: 99%